A new autumn flowering Crocus (Iridaceae) from SW Turkey: C. terzioghluii - Ciftci, Almila; Harpke, Doerte; Erol, Osman (Phytotaxa, 2019)
Crocus terzioghluii (Iridaceae) is described as a new species endemic to southwestern Anatolia, Turkey. It is related to Crocus babadagensis and differs from this species in having corm tunics with well-developed rings, and prominent stripes on outer segments, as well as in leaf number and flowering time. The corms and tunics of both species are illustrated. A phylogenetic tree obtained by Bayesian phylogenetic inference of the combined sequences of the nuclear rDNA ITS and ETS regions confirms the affiliation of C. terzioghluii to C. ser. Biflori and its close relationship to C. babadagensis. A microphotograph of the metaphase chromosomes (2n = 2x = 8) along with the idiogram and a leaf cross section of the new species are given.